Pengembangan Animasi Pembelajaran Self Safety Bencana Gempa Bumi pada Anak Usia Dini di RA Al Wildan Gondanglegi - Hikmah, Fitrotul (Universitas Al-Qolam Malang, 2025)
Earthquakes are one of the natural disasters that often occur, and procedures for understanding self-safety in early childhood at RA Al Wildan Gondanglegi require real elaboration. One of the innovations in learning with the theme of natural disasters on the topic of earthquakes is an animated video on earthquake self-safety. The research method is research and development with the ADDIE approach. The ADDIE approach includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. After the data is collected, the data analysis is carried out with the stages of data analysis, development, and product quality. Other data analysis is the analysis of student responses. The research was tested on a small scale, namely on 6 students as a pilot project, and the next experiment on 15 children. Based on the results of research conducted on animated video media on the results of children's observation responses with a score of 0.93. The teacher's response was 3.56, with categorized a feasible. So it can be concluded that the development product of earthquake self-safety animated video media is feasible for use in the learning process.